2005
DOI: 10.1002/he.178
|View full text |Cite
|
Sign up to set email alerts
|

Work/family policies in higher education: Survey data and case studies of policy implementation

Abstract: Universities reported that when work/family policies were used, they often inspired loyalty and a sense of community among faculty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 4 publications
3
46
0
Order By: Relevance
“…As both Hollenshead et al (2005) and Yoest (2004) argued, the institution's type and prestige determines the availability of policies. Using the 1994 Carnegie classification of institutional types, Hollenshead et al (2005) compared the availability of policies among research institutions, doctoral institutions, master's institutions, baccalaureate institutions, and associate institutions. They found that, on average, research institutions provided the greatest number of policies, with the 73 responding institutions averaging 2.99 policies per campus.…”
Section: Beyond Maternity Leavementioning
confidence: 97%
See 1 more Smart Citation
“…As both Hollenshead et al (2005) and Yoest (2004) argued, the institution's type and prestige determines the availability of policies. Using the 1994 Carnegie classification of institutional types, Hollenshead et al (2005) compared the availability of policies among research institutions, doctoral institutions, master's institutions, baccalaureate institutions, and associate institutions. They found that, on average, research institutions provided the greatest number of policies, with the 73 responding institutions averaging 2.99 policies per campus.…”
Section: Beyond Maternity Leavementioning
confidence: 97%
“…In their study of the benefits that 255 institutions provided to faculty, Hollenshead et al (2005) found that institutions offered programs and policies including the following: paid leave to recover from childbirth; both paid and unpaid dependent care leave; the opportunity to stop the tenure clock; a temporary reduction in teaching duties following the birth of a child; reduced, part-time, and job-share appointments; and spousal hiring programs.…”
Section: Beyond Maternity Leavementioning
confidence: 98%
“…For example, 86 percent of research institutions have formal policies to stop the tenure clock. In contrast, only 7 percent of community colleges offered the same formal policy (Hollenshead and others, 2005). In part, this difference may be due to the different requirements of earning tenure at a research institution versus a community college, an issue to which I return shortly.…”
Section: Institutional Support: How Colleges and Universities Are Resmentioning
confidence: 91%
“…The second most popular policy at community colleges is that of reduced appointment for ordinary needs. Seven percent of institutions offered such a formal policy, though an additional 17 percent reported that informal arrangements could be made to accommodate the requests of faculty (Hollenshead and others, 2005). Although informal policies offer faculty members the opportunity to make arrangements to meet their needs, they are less preferable than formal policies.…”
Section: Institutional Support: How Colleges and Universities Are Resmentioning
confidence: 95%
“…Alternatively, there is a current body of research investigating the higher-education policies that affect female faculty, especially regarding work/family issues (e.g., Hollenshead, 2005;Ward & Wolf-Wendel, 2005;Bird, 2011). Although the participants in the present study were asked about the institutional support they received as mothers from their employers' policies (i.e., parental leave, flexible scheduling, access to breastfeeding/pumping rooms), policy and institutional transformation are not the focus of this study.…”
Section: Academia and Motherhoodmentioning
confidence: 99%